Design and Development of the Folded 4-Mirror Resonators for Diode End-pumped Solid-State Cr:LiSAF Laser - Hao, Nguyen Van; Duong, Pham Van; Minh, Pham Hong; Khanh, Do Quoc; Agnesi, Antonio (Communications in Physics, 2016)
We present the design and development of folded four-mirror resonators for diode end-pumped solid-state Cr:LiSAF lasers. The astigmatic effects due to the Brewster-cut laser crystal and two curved mirrors used at oblique incidence were taken into consideration. The obtained results showed the stability regions of resonator, the beam parameters in the resonator and within the laser crystal as well as other sensitive parameters and their variation ranges. Furthermore, the designed folded four-mirror resonators for diode end-pumped Cr:LiSAF laser were experimentally evaluated. The CW Cr:LiSAF laser characteristics in threshold, efficiency and beam quality as well as comparative studies are presented.